Do consumer voices in health‐care citizens' juries matter?. (28th September 2015) - Krinks, Rachael; Kendall, Elizabeth; Whitty, Jennifer A.; Scuffham, Paul A.
Abstract: Background: There is widespread agreement that the public should be engaged in health‐care decision making. One method of engagement that is gaining prominence is the citizens' jury, which places citizens at the centre of the deliberative process. However, little is known about how the jury process works in a health‐care context. There is even less clarity about how consumer perspectives are heard within citizens' juries and with what consequences. Objectives: This paper focuses on what is known about the role of consumer voices within health‐care citizens' juries, how these voices are heard by jurors and whether and in what ways the inclusion or exclusion of such voices may matter. Results: Consumer voices are not always included in health‐care citizens' juries. There is a dearth of research on the conditions under which consumer voices emerge (or not), from which sources and why. As a result, little is known about what stories are voiced or silenced, and how such stories are heard by jurors, with what consequences for jurors, deliberation, decision‐makers, policy and practice. Discussion and Conclusion: The potential role of consumer voices in influencing deliberations and recommendations of citizens' juries requires greater attention. Much needed knowledge about the nuances of deliberative processes will contribute to an assessment of the usefulness of citizens' juries as a public engagement mechanism.